2021
DOI: 10.47467/mk.v20i2.467
|View full text |Cite
|
Sign up to set email alerts
|

Model Pembelajaran dan Implementasi Pendidikan Multikultural Dalam Pendidikan Islam dan Nasional

Abstract:   Deni Sopiansyah1, M Erihardiana2. In the world of education, there are negative impacts caused by the development of multicultural education for Indonesia's young generation, ranging from radicalism, discrimination, the loss of local culture, brawls to criminal acts from social media and the real world resulting from a lack of understanding of multicultural education in the current era. Therefore, it is important to understand the importance of understanding multicultural education for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Two articles were found on the implementation of multicultural education through local wisdom. Sopiansyah (2021) investigated that the integration of multicultural education with national identity can be achieved through (1) curriculum design that incorporates local wisdom; (2) the optimization of civic education in its efforts to strengthen national identity through multicultural and local wisdom possessed by the Indonesian people; and (3) the placement of multicultural education as an educational philosophy, educational approach, and field of study. Noor and Sugito (2019) found that children's knowledge of the significance of respecting others and diverse cultures will grow as a result of multicultural education based on local wisdom.…”
Section: Through Local Wisdommentioning
confidence: 99%
“…Two articles were found on the implementation of multicultural education through local wisdom. Sopiansyah (2021) investigated that the integration of multicultural education with national identity can be achieved through (1) curriculum design that incorporates local wisdom; (2) the optimization of civic education in its efforts to strengthen national identity through multicultural and local wisdom possessed by the Indonesian people; and (3) the placement of multicultural education as an educational philosophy, educational approach, and field of study. Noor and Sugito (2019) found that children's knowledge of the significance of respecting others and diverse cultures will grow as a result of multicultural education based on local wisdom.…”
Section: Through Local Wisdommentioning
confidence: 99%
“…Hal ini sesuai dengan pendapat (Banks dan Banks 2019) (Wilson 2012) yang menyatakan bahwa Pendidikan multicultural dapat mengajarkan mahasiswa untuk mengkaji serta menilai budaya dan etnis yang diimpelentasikan pada kegiatan pembelajaran. Terdapat beberapa ciri-ciri Pendidikan multicultural yang dilaksanakan dalam proses pembelajaran yaitu membentuk manusia yang berbudaya, mengajarkan nilai kemanusiaan, penumbuhkan etnis budaya, demokratis, dan evaluasi tingkah laku (Sopiansyah dan Erihardiana 2021).…”
Section: Gambar 2 Kegiatan Parade Budaya Pada Matakuliah Wawasan Keba...unclassified
“…Daya serap anak didik terhadap bahan yang diberikan juga bermacam-macam, ada yang cepat, ada yang sedang, dan ada yang lambat. (Kudadiri, 2019) Faktor inteligensi mempengaruhi daya serap anak didik terhadap bahan pelajaran yang diberikan oleh guru (Sopiansyah & Erihardiana, 2021). Cepat lambatnya penerimaan anak didik terhadap bahan pelajaran yang diberikan menghendaki pemberian waktu yang bervariasi, sehingga penguasaan penuh dapat tercapai.…”
unclassified